MEDIASI SIKAP PENGGUNA DAN KEMANFAATAN DALAM MANAJEMEN SISTEM INFORMASI DAERAH - Sri Maryati; Muhammad Ichsan Siregar; Anisa Listya (Jurnal Magister Akuntansi Trisakti, 2021)
The purpose of this study to test the mediation effect of user attitudes and benefits in regional information system management. One of the prerequisites for improving transparency and accountability of state financial management (central and regional) is to reform the presentation of financial statements, i.e. the government should be able to provide all relevant financial information honestly and openly to the public. Research is a quantitative research with survey method in SKPD in the Provincial Government of South Sumatra numbering 127. Data is processed with the help of WarpPLS. Based on the results of the analysis, the user attitude is able to mediate the relationship between the ease of the user to the management of regional information systems and the usefulness of being able to mediate the relationship of ease of users to the management of regional information systems